The Effect of Professional Competence and Communication Interpersonal on The Performance of State Vocational School Teachers 1 Tambun Utara - Aisyah, Sitti; Setya Handayani, Sri (Green Publisher, 2023)
The performance of a teacher is said to be good if the teacher has carried out the elements consisting of high loyalty and commitment to teaching tasks, mastering and developing subject matter, discipline in teaching and other tasks, creativity in teaching implementation, collaboration with all school members, good leadership. Be a role model for students, have a good personality, be honest, and be objective in guiding students, and be responsible for their duties. This background has drawn the author's attention to matters that affect a teacher's performance, namely professional competence and interpersonal communication. This research was conducted at SMK Negeri 1 Tambun Utara which aimed to find out how professional competence and interpersonal communication affect improving teacher performance. The sample used in this study was all teachers of SMK Negeri 1 Tambun Utara with a total of 65 teachers. Data collection using questionnaires with the range of values used is the Rikert scale. The data were analyzed using multiple regression correlation techniques using the SPSS program. Before the hypothesis test is carried out, researchers first test the validity and reliability test of the instrument to find out whether the instrument is suitable for processing. The results of the validity and reliability test show results that are in accordance with expectations so that all instruments are declared valid and realistic. The results of this study found that: 1) Professional competence affects the performance of teachers of SMK Negeri 1 Tambun Utara. 2) Interpersonal communication affects teacher performance. 3) professional competence and interpersonal communication together have an influence on the performance of teachers of SMK Negeri 1 Tambun Utara. Based on the results of research, leaders and teachers can find out that professional competence and interpersonal communication factors can actually improve teacher performance so that teachers can develop themselves in various ways and improve communication with students, colleagues, leaders and all those involved in SMK Negeri 1 Tambun Utara.